The Role of Social Capital for Increasing The Income of Paguyuban Angkutan Sepeda Motor Muria (PASMM) Members in Colo Village, Dawe Sub-District, Kudus Regency - Kusuma, Nova Indra; Soesilowati, Etty; Handoyo, Eko (Universitas Negeri Semarang, 2019)
Motorcycle incorporated in Paguyuban Angkutan Sepeda motor Muria (PASMM) or Muria Motorcycle Transportation Association is the main job of the community in Colo Village, Kudus Regency. The monopoly of PASMM in Colo Village is inseparable from a number of pilgrims in Sunan Muria. Based on this phenomenon, this study aimed at describing and analyzing socio-cultural background, social capital, and the increase in the family income of the members of PASMM motorcycle in Colo Village. The research methode used is to use a qualitative approach. Meanwhile, the data used were primary data, and secondary data. These data were collected through interviews, observation, and documentation. For the interviews, the researchers involved the members of PASMM motorcycle. They were selected using simple random sampling, and grouped into two, namely morning shift group and evening shift group. The results showed that: (1) PASMM had 391 members divided into two shifts, namely morning shift group, and evening shift group; (2) it had social capital in form of trust, norms, and network which established mutual trust among the members; (3) the income earned by the members of PASMM ranged from Rp 75,000 to Rp 150.000,00 per day. What is important from this findings was the solidarity among PASMM members to maintain the existence of PASMM from online taxi. Its existence was proved by the rule stating that the only person who is able to be PASMM member is the native people of Colo Village. The findings can contribute some significances. First, they can be a reference for the development of the use of social media. Second, they can improve the welfare of PASMM members in Colo Village.